The Silent Cry: Mysticism and Resistance - Cummings, Charles (Cistercian studies quarterly, 2004)
Reviews the book "The Silent Cry: Mysticism and Resistance," by Dorothee Soelle, translated by Barbara and Martin Rumscheidt.